WED 017 Call on me: expanding the consultant advice line for gps. Issue 10 (13th September 2018) - Richard, Ellis; Booth, James; Julie, Riley; Jen, Duffy; Martin, Wilson
Abstract : Background: The Consultant Advice Line (CAL) is a service developed to provide telephone advice for GPs within our catchment. The hours of this service were extended in early 2017 to increase its capacity for GPs seeking guidance on neurological issues as part our Neuro Network Vanguard project. Methodology: Data was routinely collected from calls received between 1 st March and 30th June 2017, and a sample of GPs completed an online survey after the call. Results: Volume of calls has more than doubled since expansion, with calls spread evenly through the week and from all CCG's in our region. Feedback from GP's was overwhelmingly positive with an average 'call usefulness' score of 9.2/10, and 100% saying they would use the service again. 40% reported the advice had avoided an outpatient referral. Discussion: The provision of equitable neurology services is challenging in the current climate. New models of care such as this help to break down barriers between primary and specialist care, reducing undesirable variation in access to acute neurology input and reducing unnecessary referrals to secondary and tertiary care.